Travellers in Africa : British travelogues, 1850-1900 - Youngs, Tim, 1961- (Manchester University Press, 2017)
This book shows how the writings of travellers in Africa during the era of Victorian exploration tell us more about nineteenth-century Britain than about Africa. The author places the narratives in their historical an cultural context, and examines how racial images may be affected by social change and literary form. Through detailed considerations of accounts of African eating habits, of the reported effects of Africa upon the objects the travellers carried with them, and of Stanley's controversial Emin Pasha Relief Expedition, depp anxieties over British social change and cultural identity are exposed. The author argues that such concerns have to be recognised in any discussion on the construction and transmission of racial stereotypes. The book closes with a consideration of Conrad's 'Heart of Darkness' as a travel narrative and contrasts Marlow's Congo with Stanley's.
Keywords: British travellers -- History -- 19th century.; Travelers -- Africa.; Africa -- Description and travel.; Voyageurs -- Afrique.; Afrique -- Descriptions et voyages.; History -- Social & cultural history.; Travel & holiday.; HISTORY -- Social History.; TRAVEL -- Africa -- General.; Travelers.; Travel.; Africa.; Social & cultural history -- Travel & holiday -- Cultural studies.; HISTORY / Social History; 1800-1899; Electronic books; History.